(x - 2) is factor of rº - 3x2 + 4x + 4
Answers
Answered by
0
Answer:
no
Step-by-step explanation:
f(x)=x-2
0=x-2
x=2
g(x)=3(2)2+4(2)+4
=12+8+4
=12+12
=24
thus x-2 is not the factor
Answered by
1
Answer:
f(x) = x-2
x-2 = 0
=> x = 2
g(x) = -3x2 + 4x + 4
=> -3 (2×2) + 4(2) + 4
=> -12 + 8 + 4
=> -4 + 4
=> 0
Ans. Yes, (x-2) is a factor of -3x2 + 4x + 4
Step by step explanation:
First we find out the value of x by applying the factor theorem. After finding out the value of x we put the value in '-3x2 + 4x + 4' and we find out that (x-2) is a factor of that equation.
Hope it helps.
Similar questions